2016
DOI: 10.1002/er.3632
|View full text |Cite
|
Sign up to set email alerts
|

The performance improvement of a cascade thermoacoustic engine by adjusting the acoustic impedance in the regenerator

Abstract: Summary A novel cascade configuration consisting of one standing wave unit and one travelling wave unit arranged in series is studied in this paper. Theoretically, a straight‐line cascade engine provides an efficient energy conversion, reduces the difficulties of fabrication and allows no Gedeon streaming. In order to achieve such a powerful cascade thermoacoustic engine, the regenerator of the travelling wave unit must be operated in high impedance and travelling wave phasing region. Various techniques of pha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 14 publications
0
12
0
Order By: Relevance
“…There are several parameters affecting the cooling performance of the travelling‐wave refrigerator, such as configurations of each component, input heating power, operating pressure, and relative locations of the subsystems; these parameters have an influence on the variation of the acoustic field in the system. Previously, only the cascade thermoacoustic engine was optimally tuned as discussed by Dhuchakallaya et al Results from the earlier study demonstrated the relationship between the configurations and geometrical dimensions of the system and acoustic impedance. In this study, several attempts have been made to evaluate the optimal configurations of the engine‐refrigerator cascaded system.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There are several parameters affecting the cooling performance of the travelling‐wave refrigerator, such as configurations of each component, input heating power, operating pressure, and relative locations of the subsystems; these parameters have an influence on the variation of the acoustic field in the system. Previously, only the cascade thermoacoustic engine was optimally tuned as discussed by Dhuchakallaya et al Results from the earlier study demonstrated the relationship between the configurations and geometrical dimensions of the system and acoustic impedance. In this study, several attempts have been made to evaluate the optimal configurations of the engine‐refrigerator cascaded system.…”
Section: Resultsmentioning
confidence: 99%
“…Due to the hybrid mode of standing wave and travelling wave in the system, the acoustic field, ie, the acoustic impedance and phase difference between pressure and velocity, needed to be adjusted properly, especially in the regenerator in order to obtain a powerful cascade engine. As discussed in Dhuchakallaya et al, the performance of the acoustic generation was improved significantly after the phase adjustment was completely implemented.…”
Section: Introductionmentioning
confidence: 99%
“…Later in 1998, Yazaki et al invented a travelling‐wave thermoacoustic prime mover and observed the spontaneous gas oscillations running around the system as a travelling wave. The thermodynamic processes executing in the travelling‐wave thermoacoustic device are based on a reversible thermodynamic cycle, consequently having the potential for higher efficiency . Nevertheless, these thermoacoustic engines typically require high‐temperature heat source (above 300°C) to initiate oscillation, which severely restricts the low‐grade heat recovery.…”
Section: Introductionmentioning
confidence: 99%
“…6 By investigating the geometrical and thermal characteristics of regenerators with different materials, Guedra et al claimed that the carbon foam was the most efficient material for the regenerator in a TWTAE. 12 From a macroscopic view, the performance of regenerator has also been improved by proposals of novel thermoacoustic configurations that help promote the thermal-to-acoustic conversion and decrease the loss, which has been the focus of many researches. They reported a maximum output acoustic power of 715 W and a highest thermoacoustic efficiency of 35.6% with the stack-type and random-fiber-type regenerators.…”
Section: Introductionmentioning
confidence: 99%
“…9,10 However, the solution to suppressing this effect was not discussed. 12,15,16 A novel looped traveling-wave thermoacoustic engine (LTWTAE) with multiple locally enlarged thermoacoustic cores (each including a regenerator sandwiched by two heat exchangers) was invented by de Blok. 11 Dhuchakallaya et al improved the acoustic field in the regenerator by inserting an appropriate pencil into the down-resonator in a cascade thermoacoustic engine.…”
Section: Introductionmentioning
confidence: 99%